Media formulation using statistical methodology to enhance α-amylase production for green synthesis of Au-NPs by Bacillus subtilis VSP4 under solid-state fermentation - Prajapati, Vimalkumar S.; Mehta, Vaibhavkumar N.; Patel, Swati K. (Frontiers in Bioengineering and Biotechnology, 2025)
In recent years, gold nanoparticles (Au-NPs) have garnered popularity for their remarkable and promising applications in various areas. Here, we report the synthesis of Au-NPs using extracellular amylase produced by Bacillus subtilis VSP4 under solid-state fermentation (SSF) through the reduction of AuCl4 with retention of enzymatic activity in the complex. Accordingly, B. subtilis VSP4 was exploited to enhance α-amylase production under SSF using the Plackett–Burman design, followed by the central composite design (CCD) of response surface methodology (RSM). According to our analysis, the most significant components in the medium are starch, yeast extract, and CaCl2 (significance >95%, ANOVA), which prominently enhance enzyme production. The optimum levels of these three selected variables were evaluated using CCD-RSM (20 runs), and it was confirmed that 0.05 g of starch, 0.1 g of yeast extract, and 5 mM of CaCl2 per 5 g of wheat bran under SSF produced the maximum α-amylase yield (169.72 U/gds). The F-value of the quadratic model (18.36) implies that the model is significant, while the F-value of the lack of fit (3.17) indicates that the lack of fit is not significant, meaning that the model has good fit. The coefficient of variance was found to be 0.369, which denotes that the experiments performed herein are reliable (R2 = 0.94) (multiple correlation coefficient), and the standard deviation for the quadratic model was found to be 4.72. We also performed separate validation experiments to confirm the adequacy of the quadratic model. The present work highlights α-amylase production by B. subtilis VSP4 under SSF, which was prominently enhanced by adopting a statistical experimental design, leading to the formation of Au-NPs of average size 5.17 ± 0.85 nm showing a surface plasmon resonance peak at 528 nm.